Response of Aeroengine with Fusing Design Suffering FBO - Chi Ma; Wei Chen; Lulu Liu; Zhenhua Zhao; Gang Luo (International Journal of Aerospace Engineering)
The loss of fan blades in an aeroengine, or fan-blade out (FBO), is a type of accident that causes a sudden imbalance and large impact load, which leads to complex vibration of a system. To conduct a dynamic analysis of an aeroengine rotor system is an important requirement for relevant departments. The purpose of this paper is to study the dynamic response of a complex dual-rotor system suffering FBO events and the protective effect of the fusing structure on the system. The dynamic model of an aeroengine dual-rotor system is established, and the response of the rotor system is obtained by calculation and analysis. The rear support bearing of the fan has a high reaction force, which may lead to bearing failure. The mechanism of a fusing structure is analyzed, and the results show that the sudden imbalance will produce impact loads on the rotor, resulting in a sharp increase in the vibration amplitude and reaction force, and then, attenuation to steady state. The fusing structure can reduce the amplitude of steady-state rotor vibration and reaction force on the support bearings. However, the transient response of the rotor will increase because of the sudden change in support stiffness.